QUERCUS FORESTS IN THE NORD IC COUNTRIES, A PRELIMINARY OVERVIEW - LAWESSON, J.E. (Annali di Botanica, 1999)
Quercus is remarkable for its wide ecological amplitude, occuring from mild, humid and oceanic settings on dunes and ledges to drier, cooler continental conditions on gravel, sand, clays and moraines. It most probably constituted a prominent component of all forests in Denmark previously, but are now mainly found on oligotrophic soils, much resembling the oak forests in the rest of the Nordic area. Only relatively few eutrophic oak forests remain intact, as Fagus sylvatica artificially has replaced oaks in many places in Denmark. A review of the principal Danish oak forest types is given, with notes on related types in Norway, Sweden and Finland.